Online travel destination recommender system with A* algorithm and content-based approach - Manos, Bryan Carlo P. (2010)
The Online Travel Destination Recommender System (OTDRS) is an online travel recommender system that provides a set of one-ay travel destination packages to the public users of the system. The generation of these travel destination packages are based on the distances between establishments and user preferences, namely, budget, preferred starting location, types of establishments the user wants to include in a package, amenities of establishments needed, number of people coming with him or her, and a preferred last stop of a travel package. The generation of travel packages consists of three phases. The first phase is a filtering phase wherein the collection of establishments are filtered based from the user?s preferred type of establishments, amenities of establishments and number of people traveling with him or her. The filtered establishments are used in the second phase of the generation of travel packages, wherein the A* algorithm is used to find the shortest path, among all the possible paths that can be produced out of the filtered establishments, from the preferred starting location to the preferred last stop of a travel package. The third and last phase filters the generated travel packages of the second phase; travel packages with a total accommodation fee less than or equal to the preferred budget are recommended to the user. Aside from the public user, the system has two other types of users ? business administrators and system administrators. Business administrators perform registration and modification of business profiles. The system administrator is responsible for the approval of the registration or modification of establishments, and managing the business administrators, types, amenities, and distances stored in the database. OTDRS gives benefits to travelers, by providing them a planned travel destination package without spending time and effort, and local business administrators, by endorsing their business to the visitors of the city. Moreover, with the development of the system, software developers are introduced to a combination of approach and algorithm used in a recommender system, which can be added to the repertoire of their knowledge
Thesis (BS Computer Science) -- University of the Philippines Mindanao, 2010
Keywords: A* algorithm; Content based approach; Travel recommender system; Web based application